Implementasi Sistem Pakar Dalam Menentukan Jenis Perawatan Kulit Wajah Menggunakan Metode Forward Chaining - petrus sokibi sukanto; Ridho Taufiq Subagio; Devie Claudea Natalie (SMATIKA JURNAL, 2019)
Clinic Charisma Skin Care provides consultation and treatment services where treatment is obtained after conducting a consultation process. The Charisma Skin Care Clinic provides free and public consultation services so that many people are interested in taking treatment. The existence of this free consultation causes treatment time to decrease due to the large number of queues. For this reason, we need a system that can speed up the consultation process. Expert System for determining the type of facial treatment based on skin type is built to help the Charisma Skin Care Clinic in conducting effective and efficient consultations. This system uses the Forward Chaining method which is a data search method that starts with the premises and produces a final conclusion. This system begins by selecting risk factors and types of symptoms and then produces skin type, skin abnormalities, treatment and serum. To build this expert system application in the design process using Ms Visio, the PHP programming language uses Notepad ++ as a text editor and uses the MySQL database with Xampp software. The results of this study are the application of expert systems to determine the type of facial skin care based on this type of skin produces the final results in the form of recommendations for treatment and serum. The advantage of this Expert System Application is that it makes it easier for patients to determine the type of treatment and serum, and can speed up the consultation process and patients can find out how much it costs to do the type of treatment and serum.